2023
DOI: 10.3390/v15040947
|View full text |Cite
|
Sign up to set email alerts
|

Use of Remdesivir in Patients with SARS-CoV-2 Pneumonia in a Real-Life Setting during the Second and Third COVID-19 Epidemic Waves

Abstract: In this retrospective comparative study, we evaluated the effectiveness of remdesivir (RDSV) in patients with SARS-CoV-2 pneumonia. Individuals hospitalized between March 2020 and August 2022 at S.M. Goretti Hospital, Latina, with a positive test for SARS-CoV-2 and, concomitantly, pneumonia, were included. The overall survival was the primary endpoint. The composite secondary endpoint included death or progression in severe ARDS at 40 days. The study population was stratified according to treatment into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Despite the prevalence of deaths due to COVID-19 constantly reducing, exploring existing treatments is crucial for future outbreaks. Marocco et al reported data on the efficacy of remdesivir, an NRTI, in people with COVID-19 who required oxygen supplementation [ 9 ]. Mussini et al reported data on the use of glucocorticoids plus tocilizumab (an IL-6 antagonist), which showed good efficacy under certain conditions [ 10 ].…”
mentioning
confidence: 99%
“…Despite the prevalence of deaths due to COVID-19 constantly reducing, exploring existing treatments is crucial for future outbreaks. Marocco et al reported data on the efficacy of remdesivir, an NRTI, in people with COVID-19 who required oxygen supplementation [ 9 ]. Mussini et al reported data on the use of glucocorticoids plus tocilizumab (an IL-6 antagonist), which showed good efficacy under certain conditions [ 10 ].…”
mentioning
confidence: 99%